Analisis Fundamental Saham LQ45 Melewati Pandemi Covid-19 - Vidada, Irwin Ananta; Saridawati, Saridawati (JURNAL ADMINISTRASI KANTOR; Vol 10 No 2 (2022): Jurnal Administrasi Kantor (Desember 2022), 2023)
The Covid-19 pandemic is known to have hit the world, including Indonesia until now. This has an impact on the stock market and economic growth. The Composite Stock Price Index (JCI) has experienced a decline, economic growth has been disrupted.Observing the extent to which the fundamental performance of the shares of companies that are included in the LQ45 index through the Covid-19 pandemic is an interesting thing to observe.The LQ45 index is an index from the Indonesia Stock Exchange which is assigned to the performance of 45 stocks that have high liquidity, large market capitalization and good company fundamentals. So it is often a choice of consideration for investors to invest.In measuring the resilience of these stocks, the author uses stock data indexed by LQ 45 on the Indonesian stock exchange from 2015 to early 2022.The sample of this research uses purposive sampling technique which checks the latest selection data for the latest LQ 45 index until the beginning of 2022.Then the sample data was obtained in the form of 11 LQ 45 indexed stock issuers that met the following criteria: 1) Companies within a period of seven years were consistently LQ45 indexed from 2015 to 2021; 2) Companies that publish annual financial reports for the period 2015 to 2021 in succession; 3) Companies in the non-financial sector; 4) Financial statements are presented in rupiah currency.The ratios used in this fundamental analysis research are EPS, PER, DER, ROA, ROE and PBV. The results show that of all the indicators used, the issuer with the best rating for PER, ROA and ROE indicators was achieved by PTBA stock issuer, the best EPS rating was achieved by INDF stock issuer, the best DER rating was achieved by KLBF stock issuer and the best PBV rating was achieved by PTPP stock issuer.   Keywords: Stock Analysis, Fundamental Analysis, LQ45 Index.